Hebrew between Jews and Christians - Kokin, Daniel Stein; Almog, Yael; Bartolucci, Guido; Burnett, Stephen G.; Campanini, Saverio; Fraade, Steven D.; Goldman, Shalom; Halperin, Liora R.; Kokin, Daniel Stein; Lange, Melanie; Resnick, Irven M.; Salvesen, Alison G.; et al. (Studia Judaica, 2023)
"Though typically associated more with Judaism than Christianity, the status and sacrality of Hebrew has nonetheless been engaged by both religious cultures in often strikingly similar ways. The language has furthermore played an important, if vexed, role in relations between the two. Hebrew between Jews and Christians closely examines this frequently overlooked aspect of Judaism and Christianity's common heritage and mutual competition."--Page 4 of cover